Apheresis buffy coat collection without photoactivation has no effect on apoptosis, cell proliferation, and total viability of mononuclear cells collected using photopheresis systems - Szczepiorkowski, Zbigniew M.; Burnett, Christine A.; Dumont, Larry J.; Abhyankar, Sunil H. (Transfusion (Philadelphia, Pa.), 2018)
BACKGROUND Extracorporeal photopheresis (ECP) has been approved for the treatment of advanced cutaneous T‐cell lymphoma since 1988. While the precise mechanisms resulting in clinical effects are not fully understood, the photoactivation of mononuclear cells (MNCs) using ultraviolet A (UVA) light and methoxsalen is believed to be the predominant initiating process. The effects of MNC passage through the instrument without photoactivation are unknown. The objective of this study was to evaluate the effect of cell processing through the photopheresis instruments on MNCs. STUDY DESIGN AND METHODS Fourteen healthy male subjects underwent one simulated ECP procedure without reinfusion of buffy coats (BCs) in a two‐center, open‐label, prospective trial. Baseline peripheral blood BC, apheresis‐separated untreated BC (BC1), and photoactivated BC (BC2) were evaluated in culture for viability by dye exclusion, apoptosis by annexin V binding, and cell proliferation response to phytohemagglutinin (PHA) stimulation by bromodeoxyuridine (BrdU) incorporation. RESULTS Photoactivation (BC2) resulted in 88% expression of annexin V by Day 1 of culture compared with 37 and 39% for baseline and untreated BC1. Cell viability by propidium iodide exclusion was reduced to 10% in BC2 on Day 1 versus 65 and 60% for baseline and BC1. The proliferative response to PHA stimulation was 97% inhibited in the photoactivated BC2. CONCLUSIONS These results demonstrate that the mechanical processes used for cell separation and processing of the BC in the absence of photoactivation do not induce a significant amount of apoptosis compared to the standard ECP with methoxsalen and UVA photoactivation.